Assessing the breeding value of nine spring field pea (Pisum sativumL.) cultivars - Kosev, Valentin; Pachev, I.; Mikić, Aleksandar (Plant Breeding and Seed Science, 2013)
The investigation was performed during the period 2007-2009 in the second experimental field of institute of Forage Crops, Pleven. Were studies follow varieties: Kristal, Picardi, Amitie, Druzba, Kerpo, Usatii 90, Rezonator, Harkovskii atalon. The variety Pleven 4 was used as a standard. According to the obtained experimental data the varieties could be classified to different groups on earliness. Early are Picardi, Amitie and Harkovskii atalonn with earliness coefficient 1.00, mid – early is Kerpo 1.38 – 1.57 and late varieties Kristal, Druzba, Pleven 4, Usatii 90, Rezonator. Harkovskii atalon is characterized with high lodging resistance only 28.61% from plants are lodging susceptible and it could be including in the future hybridization as donor of essential characters. With highest seed yield are Harkovskii atalonn (207.17 kg × da-1), Kerpo (206.08 kg × da-1) and Usatii 90 (203.33 kg × da-1) what opportunity to be included in breeding programs for high yield varieties.